A randomized controlled trial of respiratory physiotherapy in lower respiratory tract infections. (February 2020) - Marques, Alda; Pinho, Cátia; De Francesco, Silvia; Martins, Paula; Neves, Joana; Oliveira, Ana
Abstract: Introduction: Physiotherapy may play a role in the recovery of signs, symptoms and function of patients with lower respiratory tract infections (LRTI) but its effectiveness is still controversial. Objectives: To assess the effects of respiratory physiotherapy compared with standard pharmacological care on symptoms and function in outpatients with LRTI. Design: Single-blind, randomised controlled trial. Setting: Outpatients were recruited from the casualties of a central hospital. Participants: Outpatients with LRTI were recruited and randomly allocated to the control (pharmacological) or experimental (pharmacological and respiratory physiotherapy) group. Intervention: The intervention consisted of conventional pharmacological treatment and conventional pharmacological treatment plus respiratory physiotherapy. Respiratory physiotherapy included breathing and airway clearance techniques, exercise training and education during 3-weeks, 3 times per week. Main outcome measure: Primary outcome measures - occupation rate of wheezes Wh%; Secondary outcome measures - number of crackles, peripheral oxygen saturation (SpO2) modified Borg scale (mBorg), modified Medical Research Council scale (mMRC), 6-min walk test (6MWT), forced expiratory volume in 1 s and forced vital capacity, and volume and density of the lung and bronchial tree volume. Results: Ninety-seven patients (53 controls and 44 experimental) completed the intervention. After the intervention, both groups improved significantly in all variables (0.0001 < p < 0.04; 0.001<ƞ 2 <0.092), with the exception of the mBorg. The magnitude of improvement of the experimental group exceeded the control group in the number of crackles, SpO2 levels, mMRC and 6MWT (0.002 < p < 0.032; 0.002<ƞ 2 <0.092). Conclusion: Adding respiratory physiotherapy to the pharmacological treatment of outpatients with LRTI results in greater recovery of symptoms and function parameters. Trial registration: NCT02053870. Highlights: First RCT to evaluate respiratory physiotherapy in outpatients with LRTI. Respiratory physiotherapy increases SpO2 and exercise capacity in LRTI. Respiratory physiotherapy reduces no. of crackles and dyspnoea in LRTI.